2020
DOI: 10.2471/blt.19.247494
|View full text |Cite
|
Sign up to set email alerts
|

Hand-hygiene compliance by hospital staff and incidence of health-care-associated infections, Finland

Abstract: Objective To determine changes in hand-hygiene compliance after the introduction of direct observation of hand-hygiene practice for doctors and nurses, and evaluate the relationship between the changes and the incidence of health-care-associated infections. Methods We conducted an internal audit survey in a tertiary-care hospital in Finland from 2013 to 2018. Infection-control link nurses observed hand-hygiene practices based on the World Health Organization’s strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 26 publications
(31 reference statements)
5
30
0
2
Order By: Relevance
“…We found an increase in HH compliance by 5 moments across all healthcare workers and unit types with implementation of multimodal HH interventions, similar to findings of previous reports [15,18,19]. Comparing other moments and healthcare workers, HH compliance was generally lower for before touching a patient and after contact with patient surroundings, while compliance was lower among interns and cleaners.…”
Section: Discussionsupporting
confidence: 89%
“…We found an increase in HH compliance by 5 moments across all healthcare workers and unit types with implementation of multimodal HH interventions, similar to findings of previous reports [15,18,19]. Comparing other moments and healthcare workers, HH compliance was generally lower for before touching a patient and after contact with patient surroundings, while compliance was lower among interns and cleaners.…”
Section: Discussionsupporting
confidence: 89%
“…Among the SP sub-strategies, although hand hygiene is a basic practice of infection control, the adherence to hand hygiene was the lowest (below 70 points) of all SP strategies. Most previous studies have also reported similar results regarding low compliance with hand hygiene [10,23]. Moreover, in the case of no observers such as in video surveillance, hand hygiene adherence was more worse [24].…”
Section: Discussionsupporting
confidence: 65%
“…Hence, real hand hygiene adherence might be extremely low because results that excluded the observer's effect would be more realistic. Poor hand hygiene was revealed to be a risk factor for HAIs [10,18,25]. Therefore, an investigation of the barriers hindering the adherence of nurses' hand hygiene and effective strategies to improve adherence is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results in intervention effectiveness among these three clinical studies are inconclusive. Prior research in MRSA control in hospital settings suggests that hand hygiene compliance is crucial in reducing healthcare associated infections [21]. The results from our simulation also demonstrated that different level of hand hygiene compliance results in different levels of long term MRSA prevalence reduction.…”
Section: Discussionsupporting
confidence: 56%